Phylogenetic and CRISPR/Cas9 Studies in Deciphering the Evolutionary Trajectory and Phenotypic Impacts of Rice ERECTA Genes - Zhang, Yanchun; Li, Simin; Xue, Shijie; Yang, Sihai; Huang, Ju; Wang, Long (Frontiers in Plant Science, 2018)
The ERECTA family genes (ERfs) have been found to play diverse functions in Arabidopsis, including controlling cell proliferation and cell growth, regulating stomata patterning, and responding to various stresses. This wide range of functions has rendered them as a potential candidate for crop improvement. However, information on their functional roles, particularly their morphological impact, in crop genomes, such as rice, is limited. Here, through evolutionary prediction, we first depict the evolutionary trajectory of the ER family, and show that the ER family is actually highly conserved across different species, suggesting that most of their functions may also be observed in other plant species. We then take advantage of the CRISPR/Cas9 (clustered regularly interspaced short palindromic repeats–associated nuclease 9) system to assess their morphological impact on one of the most important crops, rice. Loss-of-function mutants of OsER1 and OsER2 display shortened plant stature and reduced panicle size, suggesting they possibly also functioned in regulating cell proliferation and cell growth in rice. In addition to functions similar to that in Arabidopsis, we also find clues that rice ERfs may play unique functional roles. The OsER2 displayed more severe phenotypic changes than OsER1, indicating putative differentiation in their functions. The OsERL might be of essential in its function, and the proper function of all three rice ER genes might be dependent of their genetic background. Future investigations relating to these functions are key to exploiting ERfs in crop development.